Splenic Trauma: Technical Considerations and Management of Complications - Lim, Marc Michael Del Rosario; Farsad, Khashayar (Digestive Disease Interventions, 2022)
Splenic artery embolization has become an important tool in the management of splenic trauma. This review discusses the indications, anatomy, devices, techniques, and complications associated with splenic artery embolization.
Keywords: trauma; spleen; splenic artery embolization; proximal; distal; technique; complications